From reading-writing research to practice - Briquet-Duhazé, Sophie; Turcotte, Catherine (Information systems, web and pervasive computing series, 2019)
Teachers regularly seek to update their practice with newly-developed tools from the realm of research, with the aim of applying them directly in the classroom, particularly for teaching reading and writing. Thus, teachers' continuing education is dependent on the effective dissemination and appropriation of research results.